(untitled) (Zoo Botanica, 2025)
Atherosclerosis, a major contributor to cardiovascular disorders, marked by the accumulation of plaques within arterial walls, potentially resulting in heart attacks or strokes. Considering its widespread impact, the present study explores the potential of Zinnia elegans extract in mitigating atherosclerosis in a murine model. Five groups of BALB/c mice were established: a control group, a positive control group receiving a high-fat diet (1ml/day), a drug-treated group administered Lipiget (0.2ml/day), an extract-treated group receiving Zinnia elegans (0.2ml/day), and a combined-treatment group receiving both Lipiget (0.1ml/day) and Zinnia elegans (0.1ml/day). Following a six-week induction of atherosclerosis via high-fat diet, treatments were administered for four weeks. Notably, biochemical analysis revealed significant reductions in triglyceride levels (134.5 ± 0.5 mg/dL, p < 0.05) and weight gain in the extract-treated and combined-treatment groups. Histopathological examination revealed normal tissue morphology in the plant extract treated group. These findings suggest that Zinnia elegans extract exhibits anti-atherosclerotic properties, warranting further investigation into its therapeutic potential for managing hyperlipidemia and preventing atherosclerosis.